Gamma, beta, and alpha change in individuals following a developmental assessment center - Rogers, Dawn Apryl, author; Thornton, George C., III, advisor; Chen, Peter Y., committee member; McCambridge, James A., committee member; Swaim, Randall, C., committee member (Colorado State University. Libraries, 2004)
Despite widespread application of the assessment center method to diagnosis and development, little is known about how participants' understanding of the dimensions tapped by the process is affected following their participation. Using the method outlined by Terborg, Maxwell, and Howard (1980) to measure alpha, beta, and gamma change (Golembiewski, Billingsley, & Yeager, 1976), the presence of each of these three conceptually distinct types of change was assessed for mid-level managers following participation in a developmental assessment center. In addition, the role of trait goal orientation was hypothesized as a potential correlate of change type. The results lend support to a tripartite conception of change, in that participants differentially exhibited gamma, beta, and alpha change in each of the six dimensions assessed by the center. Further, the tripartite model was found to yield substantially different conclusions than the traditional (i.e., pre versus post) measurement of change with respect to both the frequency and nature of the changes observed. Consistent with predictions, the current findings also suggest that learning orientation may be associated with beta change and performance goal orientation may be associated with alpha change. Additional supplemental analyses revealed that emotional stability, and to a lesser extent, general cognitive ability, may also be associated with the nature of the change observed. The implications of this study for both developmental assessment centers and the measurement of individual-level change are discussed.